Onlife Extremism: Dynamic Integration of Digital and Physical Spaces in Radicalization - Valentini, Daniele; Lorusso, Anna Maria; Stephan, Achim (Frontiers in Psychology, 2020)
This article argues that one should consider online and offline radicalization in an integrated way. Occasionally, the design of some counter-measure initiatives treats the Internet and the “real” world as two separate and independent entities. New information communication technologies (ICTs) allow extremists to interact simultaneously in digital and physical settings. As a result, our research contends that radicalization takes place in onlife spaces: hybrid environments that incorporate elements from individuals’ online and offline experiences. This study substantiates this claim, and it examines how algorithms structure information on social media by tracking users’ online and offline activities. Then, it analyzes how the Islamic State promoted onlife radicalization. We focus on how the Islamic State used Telegram, specific media techniques, and videos to connect the Web to the territories it controlled in Syria. Ultimately, the article contributes to the recalibration of the current debate on the relationship between online and offline radicalization on a theoretical, and on a practical, level.